Community forestry: Community methodology - McCall, Michael; Peters-Guarin, Graciela (Technical Centre for Agricultural and Rural Cooperation, 2011)
A study by the Kyoto: Think Global, Act Local project shows that using free open source software for data collection can be efficient and costeffective for forest communities.